Unmanned Hovercraft for Firefighting Based on IoT - Henna Nurdiansari; Resfiyan Tri Sukma Anggara; A. A. Istri Sri Wahyuni; Dwiyanti Margosetyowati (JEECS (Journal of Electrical Engineering and Computer Sciences), 2025)
A hovercraft is a vehicle that utilizes air pressure inside the skirt to produce an air cushion to support the entire load. It carries a ship that runs on an air cushion. Hovercrafts use propeller or fan rotation to move the hovercraft. However, there are many developments problem in hovercraft in terms of usability due to the emergence of hovercraft designs. Therefore, in this study, we propose a hovercraft as a fire extinguisher on a ship in the middle of the sea. The hovercraft frame is created using 3D printing with dimensions of 37 cm long, 30 cm wide, and 17 cm high. The hovercraft design uses a smartphone application as a remote control, which is developed using MIT App Inventor and ESP32 as a microcontroller. This hovercraft is controlled at a distance without any obstacles at 42 meters and with wall obstacles at 12 meters. The addition of DC water pump components and nozzles are used as fire extinguishers and 2 (two) servos to regulate the direction of watering, and the furthest range of watering points is at 2 meters 10 cm. The power source usage of the battery time reaches 50 minutes with active hovercraft movement. The selection of low power consumption components and lightweight 3D print materials makes this hovercraft effective in working with only a 12-volt battery and can operate for almost 2 hours.